High accuracy of the nine equivalents of nursing manpower use score assessed by critical care nurses (Swiss Medical Weekly, 2012)
PRINCIPLES: The nine equivalents of nursing manpower use score (NEMS) is frequently used to quantify, evaluate and allocate nursing workload at intensive care unit level. In Switzerland it has also become a key component in defining the degree of ICU hospital reimbursement. The accuracy of nurse registered NEMS scores in real life was assessed and error-prone variables were identified. METHODS: In this retrospective multicentre audit three reviewers (1 nurse, 2 intensivists) independently reassessed a total of 529 NEMS scores. Correlation and agreement of the sum-scores and of the different variables among reviewers, as well as between nurses and the reviewers’ reference value, were assessed (ICC, % agreement and kappa). Bland & Altman (reference value – nurses) of sum-scores and regression of the difference were determined and a logistic regression model identifying risk factors for erroneous assessments was calculated. RESULTS: Agreement for sum-scores among reviewers was almost perfect (mean ICC = 0.99 / significant correlation p